2019
DOI: 10.1093/neuros/nyz212
|View full text |Cite
|
Sign up to set email alerts
|

ABC Transporter Inhibition Plus Dexamethasone Enhances the Efficacy of Convection Enhanced Delivery in H3.3K27M Mutant Diffuse Intrinsic Pontine Glioma

Abstract: BACKGROUND An impermeable blood–brain barrier and drug efflux via ATP-binding cassette (ABC) transporters such as p-glycoprotein may contribute to underwhelming efficacy of peripherally delivered agents to treat diffuse intrinsic pontine glioma (DIPG). OBJECTIVE To explore the pharmacological augmentation of convection-enhanced delivery (CED) infusate for DIPG. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Hence, coupling of dasatinib to α v integrin-directed cRGD silica nanoparticles, which facilitates drug passage across the partially disrupted BBB in a murine GBM model, may be necessary for increasing the accumulation, retention, and diffusion of the drug [46] . An alternative strategy is convection-enhanced delivery of dasatinib in combination with the ABC transporter inhibitor tariquidar and dexamethasone, which enhanced tumor cell apoptosis and survival in a mouse model of H3.3K27M mutant diffuse intrinsic pons glioma [47] . However, the effect of dasatinib to promote a mesenchymal to amoeboid transition in a subset of cells calls for cautious monitoring of therapeutic benefits, in particular with respect to the consequence of drug treatment on local infiltration at primary and metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, coupling of dasatinib to α v integrin-directed cRGD silica nanoparticles, which facilitates drug passage across the partially disrupted BBB in a murine GBM model, may be necessary for increasing the accumulation, retention, and diffusion of the drug [46] . An alternative strategy is convection-enhanced delivery of dasatinib in combination with the ABC transporter inhibitor tariquidar and dexamethasone, which enhanced tumor cell apoptosis and survival in a mouse model of H3.3K27M mutant diffuse intrinsic pons glioma [47] . However, the effect of dasatinib to promote a mesenchymal to amoeboid transition in a subset of cells calls for cautious monitoring of therapeutic benefits, in particular with respect to the consequence of drug treatment on local infiltration at primary and metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Currently open phase 1/2 trials utilizing CED in DIPG include a study of a panobinostat nanoparticle formulation along with gadoteridol in newly diagnosed DIPG patients, as well as a trial delivering nanoliposomal irinotecan following radiotherapy [59,60]. A study open since 2011 has utilized CED to deliver a radionucleotide-antibody complex that targets the B7-H3 antigen commonly expressed by DIPG [61]. While promising, many issues remain in wider use of CED in DMG.…”
Section: Clinical Trials: Current and Future Conceptsmentioning
confidence: 99%
“…They can be co-administered with drugs to evaluate if their BBB permeability is restricted by ABC transporters, to image the transporters' function [262], or to evaluate their substrate or inhibitor interactions with ABC transporters [130], and new inhibitors are continuously under development. Furthermore, promising results have been observed when combined with other strategies for bypassing the BBB such as convection enhanced delivery [373] (Section 6.4) and nanoparticles or targeting nanocarriers (Section 6.6) [374]. Therefore, it is worthwhile to summarize them in this section.…”
Section: Strategies To Improve Cns Drug Delivery In Brain Cancermentioning
confidence: 99%
“…The use of ABC inhibitors has been suggested as a strategy to improve CED and could be further explored. For instance, a recent study showed an improvement of tumor apoptosis in a transgenic H3.3K27M mutant murine model of diffuse intrinsic pontine glioma by a pretreatment of dexamethasone plus tariquidar before convection-enhanced delivery (Section 6.5) of dasatinib [373].…”
Section: Local Delivery: Polymeric Drug Delivery Systems and Convectimentioning
confidence: 99%